Pengembangan Film Tipis ZnO/SiO2/Si untuk Aplikasi Fototermoelektrik: Sintesis dan Karakterisasi - Lia Fibriyanti; Robi Kurniawan; Chusnana Insjaf Yogihati; Eny Latifah (Postgraduate, University of Mataram, 2025)
Photothermoelectric (PTE) conversion integrates photothermal and thermoelectric effects, where light irradiation generates a temperature gradient that induces voltage through the Seebeck effect. This study examines the influence of annealing treatment on the structural, morphological, and optical properties of ZnO/SiO₂/Si thin films for PTE applications. ZnO films were synthesized on SiO₂/Si substrates modified via a hydrothermal process, with samples prepared under two conditions: without annealing and with annealing at 700, 1000, and 1100°C. X-ray diffraction (XRD) analysis showed that the unannealed sample had low crystallinity and small grain size, while annealed samples exhibited improved crystallinity and grain growth consistent with the wurtzite ZnO phase. Scanning electron microscopy (SEM-EDX) revealed that annealing transformed irregular, porous structures into more compact and uniform grains, with elemental composition approaching the stoichiometric Zn:O ratio. UV–Vis spectroscopy indicated that annealing broadened the absorption range (330–1100 nm) and reduced defect-related absorption. The enhanced crystallinity and optical absorption imply improved photothermal and thermoelectric potential. Overall, optimizing annealing temperature effectively enhances the light–heat–electricity conversion capability of ZnO/SiO₂/Si thin films for photothermoelectric device applications.